Islamic Republic of Afghanistan : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2011)
Afghanistan is one of the poorest countries in the world and, after decades of ongoing conflicts and strife, it is still at an early stage of developing its legal and institutional framework. Measures have been taken to fight crime, including financial crime. Smuggling and fraud are other major sources of illegal funds. In addition, terrorism and its financing remain a major concern. A framework has been established to allow for international mutual legal assistance but it falls short of the standard and is rarely used.